Cataract surgery today and 20 years ago - Rozegnał-Madej, Agnieszka; Żarnowski, Tomasz (Polish Journal of Public Health, 2015)
Introduction. Cataract surgery is one of the most important surgical procedures in ophthalmology.Aim. The aim of this study is to compare cataract surgeries performed in 1994 and 2014.Material and methods. A retrospective analysis of 100 cataract procedures in 1994, as well as a total of 100 cataract procedures performed in 2014. The authors considered the following factors: age, sex, vision acuity, cataract type, preoperative patient preparation, intra- and postoperative complications, and total hospitalization time.Results. Back in 1994, extracapsular cataract extraction (ECCE) was the most common treatment technique. It caused more intraoperative complications (46) and postoperative complications (38) and longer total hospitalization time (9.25 days±3.25 SD). In 2014, all procedures were performed using phacoemulsification. As a result, the number of intraoperative (20) and postoperative (14) complications has dropped significantly. Total hospitalization time was also reduced (1.53 days±1.08 SD).Conclusions. Phacoemulsification significantly improved cataract treatment. This method is much safer and more effective than ECCE.